An indigenous model for learning ultrasound-guided interventions - Khera, Pushpinder S (Medknow Publications & Media Pvt Ltd, 2014)
Ultrasound-guided interventions require good hand–eye coordination with respect to probe control and needle orientation. We describe a method of making an ultrasound phantom for practice purpose using an edible jelly mixture. The phantom is easy to make, reproducible, cheap, and simulates in vivo target.